Ultrasound-assisted vacuum drying as alternative drying method to increase drying rate and bioactive compounds retention of raspberry - Tekin-Cakmak, Zeynep Hazal; Kayacan Cakmakoglu, Selma; Avci, Esra; Sagdic, Osman; Karasu, Salih (WILEY, 2021)
This study aimed to determine the effect of different drying methods, namely hot air drying (HAD), vacuum drying (VD), ultrasound-assisted vacuum drying (USVD), and freeze drying (FD) on drying kinetic, total phenolic antioxidant activity, anthocyanin profile, in vitro-bioaccessibility of phenolic and color quality of raspberry samples. The drying time of the raspberry was 540, 720, and 1,140 min for USVD, VD, and HAD, respectively, indicating that USVD showed a significantly lower drying time than VD and HAD. The results of anthocyanin profile, TPC, CUPRAC, and DPPH analysis showed that FD had higher bioactive compound retention than other methods, followed by USVD. Cyanidin 3-O-sophoroside and Cyanidin 3-O-glucoside were found as the most abundant anthocyanin in raspberry samples. In the content of cyanidin 3-O-sophoroside, a loss of 78.33%, 15.41%, and 4.63% was observed in HAD, VD, and USVD, respectively. In vitro bioaccessibility of the VD and USVD were higher than FD and HAD. While the recovery value of TPC (%) was found for fresh raspberry as 3.09%, it was found as 6.79, 9.42, 8.46, and 5.58% for HAD, VD, USVD, and FD, respectively. Color quality was significantly affected by drying methods (p < .05), and USVD showed the lowest increment E value. SEM analysis showed that less shrinkage and cell damage were observed in FD- and USVD-dried samples. This study suggested that USVD could be used as an alternative drying method since it showed lower drying time and shrinkage, higher bioactive compounds, and color retention than VD and HAD. Practical application Raspberry is a popularly consumed fruit rich in bioactive compounds such as anthocyanin and vitamin C. Raspberry is a fruit with a low shelf life, sensitive to microorganisms and enzyme activities due to its high nutritional content and water activity. Drying is one of the most widely used methods to increase the shelf life of raspberries. It is crucial to find a suitable drying method because the bioactive components, color, and physical structure may change during drying. In this study, the effects of four drying methods on the total bioactive components, anthocyanin profile, microstructural structure, color, and phenolic antioxidant in vitro bioaccessibility of raspberry fruit were investigated. The study contains original data.
Keywords: IN-VITRO BIOACCESSIBILITY; ANTIOXIDANT CAPACITY; RED RASPBERRY; MATHEMATICAL-MODEL; DEHYDRATION; POLYPHENOLS; QUALITY; ANTHOCYANINS; PHENOLICS; EXTRACTS; Food Science & Technology